2018
DOI: 10.1007/s00261-018-1682-1
|View full text |Cite
|
Sign up to set email alerts
|

MR texture analysis: potential imaging biomarker for predicting the chemotherapeutic response of patients with colorectal liver metastases

Abstract: MR texture features on pre-treated T2 images have the potential to predict the therapeutic response of colorectal liver metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 26 publications
0
40
0
Order By: Relevance
“…Most papers ( n = 28) described retrospective analyses, while four reported planned secondary analyses of prospectively acquired data [ 32 , 33 , 34 , 35 ]. Nineteen authors analyzed computed tomography (CT) [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ], eight magnetic resonance imaging (MRI) [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ], three positron-emission tomography (PET)/CT [ 59 , 60 , 61 ], and two multiple imaging modalities (CT and MRI; PET and MRI, respectively) [ 62 , 63 ]. Various software applications were used for texture analysis, with these being custom-made in a large proportion of cases ( n = 10).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most papers ( n = 28) described retrospective analyses, while four reported planned secondary analyses of prospectively acquired data [ 32 , 33 , 34 , 35 ]. Nineteen authors analyzed computed tomography (CT) [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ], eight magnetic resonance imaging (MRI) [ 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ], three positron-emission tomography (PET)/CT [ 59 , 60 , 61 ], and two multiple imaging modalities (CT and MRI; PET and MRI, respectively) [ 62 , 63 ]. Various software applications were used for texture analysis, with these being custom-made in a large proportion of cases ( n = 10).…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies analyzed the association between radiomic features and response to chemotherapy [ 32 , 33 , 37 , 38 , 40 , 45 , 46 , 54 , 56 , 61 ]. Evidence mainly regarded patients receiving anti-VEGF treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Liang et al [29] found that the value of Mean from the ADC maps of the responding group were significantly lower than that of the non-responding group in colorectal liver metastases. A latest study [30] exhibited that the higher Entropy, Contrast and the lower Correlation were independently associated with a better chemotherapeutic response in colorectal liver metastases.…”
Section: Prediction Of Therapeutic Effect Of Primary Lesionsmentioning
confidence: 99%